La littérature de l’entre-deux et le regard sur la langue française. Enjeux linguistiques et identitaires dans l'oeuvre de Fouad Laroui (Altre Modernità, 2020)
Fouad Laroui, a talented Moroccan author who writes in French and at times Dutch, is an exemplar of the in-between – in fact, the in-between-several-cultures. Like many Moroccans, he is “neither here nor there”. His original work, notable for the author’s dual belonging as well as its highly ironic vein, embodies multiple facets of multiculturalism, which he experienced during his youth at the French “lycée” in Casablanca, his trips to the western world (he now lives in Amsterdam) and through openness to European cultures. His stories in French are enriched with diverse references, resulting in a sort of patchwork – a jumble of words where the French language is present, but it is coloured by other languages and literary reminiscences (Laroui cited in Martin & Drevet 107).This article reflects on the author’s relationship with the French language and culture, by analysing the sense of identity and search for identity of his characters whose connections with France, and the western world, are marked by conflicting feelings, bearing traces of the Maghreb authors’ own sense of being torn. Is French an instrument of oppression or emancipation? The article focuses on two representative works, “Le jour où Malika ne s’est pas mariée” (2009) and “Une année chez les Français” (2010), set against the complex, multilingual backdrop of Morocco as discussed in his essay “Le drame linguistique marocain” (2011).